Pengaruh Relaksasi Nafas dalam Terhadap Kecemasan Pasien Pre Operasi Fraktur - Banjarnahor, Purnama; Sulidah, Sulidah (Universitas Malahayati, 2024)
ABSTRACT Fracture surgery is an invasive procedure that induces anxiety in patients. Preoperative anxiety has a negative impact on the success of the procedure and treatment; it can even lead to the postponement or cancellation of the surgery. Concrete efforts are needed to manage preoperative anxiety in patients to prevent further harm. This study aims to identify the level of preoperative anxiety in fracture patients, before and after practicing deep breathing relaxation; and to analyze the effect of deep breathing relaxation on preoperative anxiety in fracture patients. This research is a quantitative study with a pre-experimental design of the One Group Pre Test-Post Test Design. The population of this study is all preoperative fracture patients, with a known population size from medical record data in the last 3 months of 79 people. The sample was calculated using the Slovin formula, resulting in 45 respondents selected using accidental sampling technique. Respondents' anxiety was measured using the Hamilton Rating Scale for Anxiety instrument developed by the Jakarta Biological Psychiatry group in the form of an Anxiety Analog Scale with a Cronbach's Alpha value of 0.794. This study was able to identify preoperative fracture patients experiencing anxiety; anxiety decreased after practicing deep breathing relaxation. Statistical analysis using Pearson product-moment correlation showed that deep breathing relaxation had a positive effect in reducing preoperative anxiety in fracture patients. Keywords: Anxiety, Fracture, Deep Breathing Relaxation, Preoperative ABSTRAK Operasi fraktur merupakan prosedur invasif yang menimbulkan perasaan cemas pada pasien. Kecemasan pre operasi mempunyai pengaruh negative terhadap keberhasilan prosedur dan perawatan; bahkan dapat menyebabkan ditunda atau dibatalkannya prosedur operasi. Perlu upaya konkrit mengelola kecemasan pasien pre operasi agar tidak menimbulkan kerugian lebih jauh bagi pasien. Penelitian ini bertujuan untuk mengidentifikasi tingkat kecemasan pasien pre operasi fraktur, sebelum dan sesudah melakukan relaksasi nafas dalam; serta menganalisis pengaruh relaksasi nafas dalam terhadap kecemasan pasien pre operasi fraktur. Penelitian ini merupakan studi kuantitatif dengan desain pre eksperimental rancangan One Group Pre Test-Post Test Desaign. Populasi penelitian ini ialah seluruh pasien pre operasi fraktur dengan besar populasi diketahui dari data rekam medis 3 bulan terakhir sebesar 79 orang. Sampel dihitung dengan rumus Slovin diperoleh 45 responden yang diambil dengan teknik accidental sampling. Kecemasan responden di ukur dengan instrumen Hamilton Rating Scale for Anxiety yang sudah dikembangkan oleh kelompok Psikiatri Biologi Jakarta dalam bentuk Anxiety Analog Scale dengan nilai Cronbach’s Alpha 0,794. Penelitian ini mampu mengidentifikasi pasien pre operasi fraktur mengalami kecemasan; kecemasan menurun setelah melakukan relaksasi nafas dalam. Analisis statistic dengan person product moment terbukti relaksasi nafas dalam berpengaruh positif dalam menurunkan kecemasan pasien pre operasi fraktur. Kata Kunci: Fraktur, Kecemasan, Pre operasi, Relaksasi Nafas Dalam.